Pyrazine based novel molecules as potential therapeutic agents: Synthesis, in vitro biological screening, in silico ADMET profiling and molecular docking study - Rafaqat Hussain; Wagma Hassan; Fazal Rahim; Shazia Subhan; Zakia Subhan; Shoaib Khan; Amjad Hussain; Hayat Ullah; Muhammad Nabi; Riaz Ullah; Essam A. Ali; Saltanat Aghayeva (Results in Chemistry, 2024)
The current study described the synthesis of pyrazine-based novel molecules (1–15) using stepwise processes and their structures have been identified using various characterization techniques such as 1HNMR, 13CNMR, and HREI-MS. Furthermore, biological assessment of these scaffolds as anti-Alzheimer, anti-bacterial, and anti-fungal activities were evaluated. Their inhibitory potentials were determined using the minimum inhibitory concentration (MIC) in the presence of standard drugs donepezil (IC50 = 8.90 ± 0.20 µM), streptomycin (inhibition = 36.5 %), and Terbinafine (inhibition = 31.7 %) respectively. Among the screened molecules against acetylcholinesterase enzyme, the potent behavior was shown by scaffolds 1 (IC50 = 3.20 ± 0.40 µM), 2 (IC50 = 2.10 ± 0.20 µM), 4 (IC50 = 2.90 ± 0.10 µM), 5 (IC50 = 5.80 ± 0.30 µM), 6 (IC50 = 7.20 ± 0.20 µM), 8 (IC50 = 6.30 ± 0.30 µM), 9 (IC50 = 6.50 ± 0.20 µM), 10 (IC50 = 7.30 ± 0.20 µM) and 11 (IC50 = 7.10 ± 0.20 µM). Structure-activity relationship was carried out which mainly depends upon the substitution pattern around the phenyl ring. These compounds were further investigated by molecular docking studies which explore the binding interaction of ligands with active sites of enzymes. Moreover, ADMET prediction was also studied for potent scaffolds that displayed drug-like properties.